2017
DOI: 10.18632/oncotarget.23694
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling identified differentially expressed genes and pathways associated with tamoxifen resistance in human breast cancer

Abstract: was applied to analyze the association of ER signal pathway with the 10 DEGs. 3 significant genes (GFRA3, NPY1R and PTPRN2) were closely related to ER related pathway. These significant DEGs regulated many biological activities such as cell proliferation and survival, motility and migration, and tumor cell invasion. The interactions between these DEGs and drug resistance phenomenon need to be further elucidated at a functional level in further studies. Based on our findings, we believed that these DEGs could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Although CpG sites were not identical in all studies, DNAm changes at other loci in PTPRN2 and ABLIM2 were observed in two [(45) and the present study]. Recently, PTPRN2 has been identified as a possible obesity susceptibility gene (46), and its tumor expression was reported as a novel candidate biomarker and therapeutic target in estrogen receptor-positive breast cancer (47). Concerning the ABLIM2 gene, little is known besides its potential role in lung cancer metastasis (48) and regulation by estradiol (49).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Although CpG sites were not identical in all studies, DNAm changes at other loci in PTPRN2 and ABLIM2 were observed in two [(45) and the present study]. Recently, PTPRN2 has been identified as a possible obesity susceptibility gene (46), and its tumor expression was reported as a novel candidate biomarker and therapeutic target in estrogen receptor-positive breast cancer (47). Concerning the ABLIM2 gene, little is known besides its potential role in lung cancer metastasis (48) and regulation by estradiol (49).…”
Section: Discussionmentioning
confidence: 42%
“…In the literature, DNAm of PTPRN2 and HOXA3 gene expression have both been associated with obesity (71,72). Furthermore, DNAm of PTPRN2, HOXA3, C1orf70 and expression of PTPRN2, ABLIM2, NCKAP5 and LY6D have been linked to various cancers (48,(73)(74)(75)(76)(77)(78) including breast cancer (47,79).…”
Section: Discussionmentioning
confidence: 99%
“…These analyses showed that the most DEGs were enriched in binding category (more than 40% of 5,660 genes) [55]. Similarly, Men et al showed that a high proportion of DEGs found between tamoxifen-sensitive and tamoxifen-resistant MCF-7 breast cancer cell line belonged to the binding subcategories (2,836 genes, representing 93.35% of all DEGs) [56]. Moreover, Fang et al also found a high proportion of DEGs within the binding category (946 genes, representing 89.16% of all DEGs) when CDDP-resistant lung adenocarcinoma cell line A549 was compared to its parental A549 cell line [54].…”
Section: Discussionmentioning
confidence: 89%
“…[ 31 ] (which uses random forest approach as a base), and mRNA data alone (without considering molecular pathways) and demonstrated that our method outperforms these techniques in predicting risk of resistance to tamoxifen. Furthermore, we have compared our pathway signature to other known signatures of tamoxifen response [18] , [19] , [20] and have shown the superiority of our pathway-based approach (adjusted hazard ratio = 3.11, hazard p-value = 0.0278). Finally, to enhance clinical applicability of our finding, we derived five read-out genes (each of which reflects activity changes in a corresponding pathway) and defined their treatment failure scoring system, indicating risk of developing tamoxifen resistance in two patient cohorts (Test cohort 1, adjusted hazard ratio = 3.1; Test cohort 2, adjusted hazard ratio = 6.95).…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, several groups have developed gene expression signatures of tamoxifen response for ER+ patients, including 10 gene-signature by Men et al. [ 18 ], 21 gene-signature by Paik et al. [ 19 ] (known as Oncotype DX), and 2 gene-signature by Ma et al.…”
Section: Introductionmentioning
confidence: 99%